2014
DOI: 10.1007/s00268-014-2762-1
|View full text |Cite
|
Sign up to set email alerts
|

No Patients to Resect or Transplant: An Analysis of Patients with Hepatocellular Carcinoma Admitted to a Major African Referral Hospital

Abstract: The majority of HCC in our population is caused by HBV. Up to 61 % of patients may be eligible for curative treatment, transarterial chemoembolization, or sorafenib treatment. This percentage may be increased with a robust surveillance program for patients at increased risk for HCC. Hepatitis B vaccination must also be a public health priority.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
10
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 23 publications
4
10
0
Order By: Relevance
“…Yang et al in 2017 reported that 84% of liver cancer cases presented with multinodular disease (9). In Ghana, Gyedu et al found that only 8% of persons with HCC seen at the Komfo Anokye Teaching Hospital in Accra between 2007-2013 were eligible for curative treatment (10). In our study, the AFP performed well as a diagnostic test in the detection in HCC.…”
Section: Discussionsupporting
confidence: 62%
“…Yang et al in 2017 reported that 84% of liver cancer cases presented with multinodular disease (9). In Ghana, Gyedu et al found that only 8% of persons with HCC seen at the Komfo Anokye Teaching Hospital in Accra between 2007-2013 were eligible for curative treatment (10). In our study, the AFP performed well as a diagnostic test in the detection in HCC.…”
Section: Discussionsupporting
confidence: 62%
“…This study confirms the important contribution of HBV to HCC in Ghana as in many other SSA countries [ 2 , 12 ]. HBsAg positivity of 71.7% is higher than 52% previously reported in 2015 from Kumasi in Ghana and 60% from The Gambia and 48% from Ethiopia, both of which also have very high population prevalence of HBV [ 9 , 11 , 15 ]. The positive aspect to this finding is that HCC in Ghana remains a largely preventable cancer if the appropriate HBV control measures like childhood vaccination as in Taiwan and access to antiviral therapy can be effectively implemented [ 16 , 17 ].…”
Section: Discussionmentioning
confidence: 72%
“…These findings may be a reflection of the need for building cancer‐specific surgical capacity aimed at improving outcomes for the increasing number of cancer patients in SSA. They may also be the consequence of the often documented late‐stage presentation among cancer patients in SSA …”
Section: Discussionmentioning
confidence: 99%
“…They may also be the consequence of the often documented late-stage presentation among cancer patients in SSA. [25][26][27][28][29] Adequate staging was available for only 40% of patients who had a tissue or radiologically confirmed diagnosis of cancer. This is consistent or better than reports from other SSA countries like Uganda, The Gambia, and Malawi 11,23,30,31 ; however it is less than the 50% reported from Pakistan, another LMIC country.…”
Section: F I G U R Ementioning
confidence: 99%